Influence of Glycine and Arginine on Cylindrospermopsin Production and aoa Gene Expression in Aphanizomenon ovalisporum - Ángel Barón-Sola; Francisca Fernández del Campo; Soledad Sanz-Alférez (Toxins, 2017)
Arginine (Arg) and glycine (Gly) seem to be the only substrates accepted by the amidinotransferase that catalyze the first step of the synthesis pathway of the cyanotoxin cylindrospermopsin (CYN), leading to guanidinoacetate (GAA). Here, the effect of these amino acids on the production of CYN in cultures of the cylindrospermopsin-producing strain, Aphanizomenon ovalisporum UAM-MAO, has been studied. Arg clearly increased CYN content, the increment appearing triphasic along the culture. On the contrary, Gly caused a decrease of CYN, observable from the first day on. Interestingly, the transcript of the gene ntcA, key in nitrogen metabolism control, was also enhanced in the presence of Arg and/or Gly, the trend of the transcript oscillations being like that of aoa/cyr. The inhibitory effect of Gly in CYN production seems not to result from diminishing the activity of genes considered involved in CYN synthesis, since Gly, as Arg, enhance the transcription of genes aoaA-C and cyrJ. On the other hand, culture growth is affected by Arg and Gly in a similar way to CYN production, with Arg stimulating and Gly impairing it. Taken together, our data show that the influence of both Arg and Gly on CYN changes seems not to be due to a specific effect on the first step of CYN synthesis; it rather appears to be the result of changes in the physiological cell status.